Model Ilmu Perilaku dalam Pendidikan: Analisis Pemodelan Persamaan Struktural (SEM) tentang Kecerdasan Emosional, Iklim Sekolah, dan Disiplin Guru pada Anak Usia Dini - Wiwik Setyowati; Joko Sutarto; Diana (Postgraduate, University of Mataram, 2025)
This study addresses the problem of low teacher discipline in early childhood education (ECE), which is influenced by various psychological and organizational factors. The research aimed to analyze the relationships among emotional intelligence, school climate, work motivation, and teacher discipline. A mixed-methods approach was used involving 100 ECE teachers in Semarang City selected through purposive sampling. Quantitative data were obtained through standardized questionnaires and analyzed using structural equation modeling (SEM), while qualitative data were collected through semi-structured interviews with teachers and principals. SEM analysis showed a good model fit (χ²/df = 1.89; CFI = 0.95; TLI = 0.94; RMSEA = 0.052). Emotional intelligence significantly affected work motivation (β = 0.41, p < 0.001) and teacher discipline (β = 0.34, p = 0.001). School climate also significantly influenced work motivation (β = 0.38, p < 0.001) and discipline (β = 0.29, p = 0.003). Work motivation had a positive effect on teacher discipline (β = 0.30, p = 0.001) and partially mediated the effects of emotional intelligence and school climate. The study concludes that strengthening emotional intelligence, building a supportive school climate, and enhancing work motivation are essential strategies to improve teacher discipline in ECE settings.